Treatment Preferences for Acute Allergic Reactions: A Discrete Choice Experiment - Sofia Löfvendahl; Emelie Andersson; Sara Olofsson; Karin Wahlberg; Leif Bjermer; Göran Tornling; Jonas Hjelmgren (Journal of Health Economics and Outcomes Research, 2024)
# Background Timely treatment of acute allergic reactions (AARs) is important to minimize reaction severity. Corticosteroid tablets dissolved in water are commonly used in mainstay treatment. A new oral film that dissolves on the tongue provides a faster and less cumbersome alternative to tablets for corticosteroid administration during AARs. This study evaluated patients’ preferences for attributes related to administration mode of corticosteroids in AARs.